Complete mitochondrial genome assembly and comparative analysis of Colocasia esculenta - Huinan Li; Lili Liu; Zuyang Qiu; Fanglian He; Weiqing Dong (BMC Plant Biology)
Abstract Colocasia esculenta ranks as the fifth most important tuber crop and is known for its high nutritional and medicinal value. However, there is no research on its mitochondrial genome, hindering in-depth exploration of its genomic resources and genetic relationships. Using second- and third-generation sequencing technologies, we assembled and annotated the mitogenome of C. esculenta. Its mitogenome mainly consists of five circular DNA molecules, with a total length of 594,811 bp and a GC content of 46.25%. A total of 55 genes, 157 simple sequence repeats, 29 tandem repeat sequences, 202 dispersed repeat sequences, and 625 RNA editing sites were detected. Most protein-coding genes use ATG as the start codon, and the third position of the codon tends to be A or T (U). GAA, AUU, and UUU are the most common codons in C. esculenta mitochondria. Finally, based on 28 representative plant species, a phylogenetic tree was constructed, revealing a close relationship between C. esculenta and Araceae. This study provides comprehensive information on C. esculenta, laying a foundation for crop genetics and molecular breeding.